Prevalence and influencing factors of different types of obesity among middle-aged and elderly Han and Tibetan residents in Gansu province: a cross-sectional study - Qian ZHANG; Binguo YAN; Tianhui TANG; Hangzhao FAN; Yi ZHAO; Yaqiong WANG; Ziyuan GAO; Jiahao HU; Leilei PEI; Fangyao CHEN; Shaonong DANG; Xinhua WANG; et al. (Editorial Office of Chinese Journal of Public Health, 2024)
Objective To understand the prevalence and influencing factors of different types of obesity among middle-aged and elderly Han and Tibetan residents in Gansu province, and to provide evidence for the prevention and control of obesity. Methods Data of 18 114 middle-aged and elderly adults aged 35 to 75 years old with complete body measurement information were analyzed. The data were collected in the baseline survey of "Gansu Province's Urban and Rural Natural Population Cohort Establishment and Tumor Follow-up Study" of the "Regional Ethnic Cohort Study in Northwest China" conducted from November 2018 to May 2019. Body mass index (BMI), waist circumference (WC), body fat percentage (BFP) and visceral fat index (VFI) were used to assess the prevalence of general obesity, central obesity, body fat obesity, and visceral obesity, respectively. Multivariable unconditional logistic regression analyses were used to explore the influencing factors of different types of obesity. Results Among the 18 114 middle-aged and elderly adults enrolled in Gansu Province, there were 16 999 Han (93.8%) and 1 115 Tibetan (6.2%) ones. The prevalence rates of general obesity, central obesity, body fat obesity, and visceral obesity among middle-aged and elderly Han and Tibetan residents were 12.5% and 9.0%, 31.4% and 33.9%, 50.7% and 41.9%, 40.0% and 27.7%, respectively. The prevalence rates of general obesity, body fat obesity, and visceral obesity among Han adults were higher than those among Tibetan residents (all P < 0.05). The results of multivariable unconditional logistic regression analysis showed that being female was a risk factor for body fat obesity among middle-aged and elderly Han residents and for general obesity, central obesity, and body fat obesity among middle-aged and elderly Tibetan residents in Gansu province, but was a protective factor for general obesity, central obesity, visceral obesity among middle-aged and elderly Han residents and for visceral obesity among middle-aged and elderly Tibetan residents in Gansu province. Age ≥ 45 years old was a risk factor for general obesity, central obesity, body fat obesity, and visceral obesity among middle-aged and elderly Han residents and for body fat obesity among middle-aged and elderly Tibetan residents in Gansu province. Primary school education and above was a protective factor for central obesity among middle-aged and elderly Han residents in Gansu province. Being married was a risk factor for general obesity and visceral obesity among middle-aged and elderly Han residents in Gansu province. Being a non-farmer was a risk factor for general obesity and central obesity among middle-aged and elderly Han residents in Gansu province. Per capita annual household income ≥ 4 000 Yuan was a risk factor for visceral obesity among middle-aged and elderly Han residents in Gansu province. Smoking was a protective factor for general obesity, body fat obesity, and visceral obesity among middle-aged and elderly Han residents in Gansu province. Drinking was a risk factor for central obesity among middle-aged and elderly Tibetan residents in Gansu province. ConclusionThe prevalence rates of general obesity, body fat obesity, and visceral obesity were higher among middle-aged and elderly Han residents than those among middle-aged and elderly Tibetan residents in Gansu province, and gender was a common influencing factor for the four types of obesity among middle-aged and elderly Han and Tibetan residents in Gansu province.